School distress and the school attendance crisis: a story dominated by neurodivergence and unmet need - Connolly, Sophie E.; Constable, Hannah L.; Mullally, Sinéad L. (Frontiers in Psychiatry, 2023)
Background: The Covid-19 pandemic has brought into sharp focus a school attendance crisis in many countries, although this likely pre-dates the pandemic. Children and young people (CYP) struggling to attend school often display extreme emotional distress before/during/after school. We term this School Distress. Here we sought to elucidate the characteristics of the CYP struggling to attend school in the UK. Methods: Using a case-control, concurrent embedded mixed-method research design, 947 parents of CYP with experience of School Distress completed a bespoke online questionnaire (February/March 2022), alongside an aged-matched control group (n=149) and a smaller group of parents who electively home-educate (n=25). Results: In 94.3% of cases, school attendance problems were underpinned by significant emotional distress, with often harrowing accounts of this distress provided by parents. Whilst the mean age of the CYP in this sample was 11.6 years (StDev 3.1 years), their School Distress was evident to parents from a much younger age (7.9 years). Notably, 92.1% of CYP currently experiencing School Distress were described as neurodivergent (ND) and 83.4% as autistic. The Odds Ratio of autistic CYP experiencing School Distress was 46.61 (95% CI [24.67, 88.07]). Autistic CYP displayed School Distress at a significantly earlier age, and it was significantly more enduring. Multi-modal sensory processing difficulties and ADHD (amongst other neurodivergent conditions) were also commonly associated with School Distress; with School Distress CYP having an average of 3.62 NDs (StDev 2.68). In addition, clinically significant anxiety symptomology (92.5%) and elevated demand avoidance were also pervasive. Mental health difficulties in the absence of a neurodivergent profile were, however, relatively rare (6.17%). Concerningly, despite the striking levels of emotional distress and disability reported by parents, parents also reported a dearth of meaningful support for their CYP at school. Conclusion: Whilst not a story of exclusivity relating solely to autism, School Distress is a story dominated by complex neurodivergence and a seemingly systemic failure to meet the needs of these CYP. Given the disproportionate number of disabled CYP impacted, we ask whether the UK is upholding its’ responsibility to ensure the “right to an education” for all CYP (Human Rights Act 1998).